Assessment of the of effectiveness of internal audit on local government authorities in Tanzania: Case of Mufindi District Council - Anthony, Erick (Mzumbe University, 2023)
A Dissertation Submitted in Partial Fulfillment of the Requirements for the Award of the Degree of Master of Science in Accounting and Finance (MSc. A& F) of Mzumbe University